Analysis of Notaries As Public Officials Who Have Been Declared Bankrupt from the Perspective of Notarial Law - Fajri Yandi; Teuku Abdurrahman; Sri Walny Rahayu (Genesis Law and Social Sciences, 2025)
Notaries play an important role in the Indonesian legal system, but the Notary Law does not regulate the dismissal of a Notary due to bankruptcy. This ambiguity gives rise to multiple legal interpretations regarding whether a Notary appointed by the State can be dishonorably dismissed in the context of bankruptcy. This study aims to analyze the interpretation of the dismissal of a Notary who is declared bankrupt and its legal consequences for the Notary's authority. The method used is normative juridical legal research with a conceptual, legislative, and analytical approach. The study results indicate that the provisions in Article 9 paragraph (1) and Article 12 letter a of the Notary Law give rise to legal uncertainty and are contrary to the principle of justice because bankruptcy is a civil matter and is not always related to violations of job ethics. This study suggests revising and eliminating these articles to overcome multiple interpretations, ensure fair legal protection for Notaries, and maintain the dignity of the Notary's position in the Indonesian legal system.